Impact of Covid-19 on Readymade Garments Workers at Dhaka Division Of Bangladesh - Rabi Ullah, Muhammad (Advances in Social Sciences Research Journal, 2024)
In this study we are attempts to identify the real situation of COVID-19 impact on working environment of RMG workers in Bangladesh. The consequences of the COVID-19 pandemic impact on RMG workers is dire and include uncertainty about the wages during the COVID-19 pandemic and related issues such as lack of money for essentials such as food, and concerns about the re-opening of factories during COVID-19 infection peak times. The objectives of this study is to identify the COVID-19 impact on readymade garments (RGM) workers as well as shows the present conditions of readymade garments workers and work place environment of RMG sector in Bangladesh. Finally, to find out the problems and suggest some policy recommendations of RMG sectors in Bangladesh. This study attempts to know COVID-19 Impact on working environment of RMG workers in Bangladesh in Selected Factories in Dhaka division. The present study is an exploratory sample survey. Besides this, to enhance the acceptance of result and considering the circumstances few case studies are also conducted. The sampling of my study is 50 workers selected based on accidental sampling techniques and five garments selected based on sample survey and purposively out of the total population of these garments industries. The sources of data to carry out the proposed study data has been collected from two sources; Primary and Secondary sources. The data processing with various tables, pie-charts, bar-diagrams and figures have been used for analyzing the collected data. The information have been classified and tabulated under various characteristics. The results have been shown using simple statistical methods, qualitative and quantitative both kinds of analysis have been used. Some problems and limitations are therefore, inevitable in the way of conducting such a broad task. Finding of this study are most of the workers have lost their overtime work. Their income level falls that result, domestic violence has raised in most of the workers families. At last we can say that the production of clothing during the COVID-19 pandemic must not go ahead without an urgent overview of the system and the development of a plan to ensure the health and safety of workers.